Digital Transformation in the Arts Field: Creating New Collaborations in the Digital Arts World - Yuniana Cahyaningrum; Muhammad Ridwan Putra Wijaya (Smart International Management Journal, 2024)
Digital transformation has become a major catalyst in changing the way artists create and collaborate in the art world. This article examines how technological advances, including artificial intelligence (AI), augmented reality (AR), virtual reality (VR), and blockchain, are creating new collaborative opportunities for artists. These technologies not only expand the mediums and methods of artistic expression but also introduce new ways for artists to interact and collaborate, both locally and globally. Through analysis of various case studies and interviews with artists, this article reveals the significant impact of digitalization on the creative process and distribution of works of art. In addition, this article also highlights the challenges faced in adopting digital technology, including copyright issues, data security, and changing art market dynamics. In doing so, this article provides a comprehensive view of how digital transformation is driving collaboration and innovation in the arts world, as well as its implications for the future of the arts industry.